European yearbook of international economic law 2011 - Herrmann, Christoph S. 1966-; Terhechte, Jörg Philipp; SpringerLink (Online service). (Berlin Heidelberg New York Springer, 2011)
Part one of Vol. 2 (2011) of the European Yearbook of International Economic Law adresses two major topics of current academic debate and public interest: firstly, it focuses on the State and the Global Economy, secondly, on Climate Change and International Economic Law. Part two contains treatises of recent regional integration developments taking place in the major regions of the world. Part three covers the legal and political developments in the major international organizations and fora dealing with international economic policy making. Part four contains book reviews of recent works in the field of International Economic Law
Part I: Topics Special Focus I The State and the Global Economy Distinguished Essay Governmental Decision-Making in the World Economy Karl M. Meessen Central Bank Challenges in the Global Economy Fabian Amtenbrink An International Normative Framework for Sovereign Wealth Funds? Ludwig Gramlich Sovereign Wealth Funds: Market Investors or "Imperialist Capitalists"? The European Response to Direct Investment by Non-EU State-Controlled Entities Heike Schweitzer The Role of the IMF as a Global Financial Authority Rosa M. Lastra No Ado About Nothing: Obama's Trade Policies After 1 Year Andreas Falke Special Focus II: Climate Change and International Economic Law Carbon Capture and Storage from the Perspective of International Law Alexander Proelss and Kerstin Güssow Biofuels and WTO Law Wolfgang Weiß Climate Labelling and the WTO: The 2010 EU Ecolabelling Programme as a Test Case Under WTO Law Erich Vranes Environmental Services and the General Agreement on Trade in Services (GATS): Legal Issues and Negotiating Stakes at the WTO Mireille Cossy European Union Competences and Actions in International Environment Law: Recent Developments and Current Challenges Kirstyn Inglis Part II: Regional Integration The European Union and Regional Trade Agreements: A Case Study of the EU-Korea FTA Colin M. Brown MENA: The Question of Palestinian Observership and Accession to the WTO Tomer Broude Integration and Disintegration in North America: The Rise and Fall of International Economic Law in One Region Stephen Clarkson African Regional Economic Integration: Is the Paradigm Relevant and Appropriate? Colin McCarthy Regional Integration in Latin America: Some Lessons of 50 Years of Experience Félix Peña Report on the ASEAN Economic Cooperation and Integration Prasit Aekaputra Part III: International Economic Institutions From the G8 to the G20: Reforming the Global Economic Governance System Claudia Schmucker and Katharina Gnath The Doha Development Agenda at a Crossroads: What Are the Remaining Obstacles to The Conclusion of the Round: Part II? Edwini Kessie WTO Dispute Settlement -- The Establishment of 'Binding Guidance' by the Appellate Body in US Stainless Steel and Recent Dispute Settlement Rulings Andreas Krallmann Part IV: Book Reviews Rudolf Dolzer, Christoph Schreuer, Principles of International Investment Law Marc Bungenberg Daniel Wüger and Thomas Cottier, Genetic Engineering and the World Trade System Hans-Georg Dederer Simon Lester and Bryan Mercurio with Arwel Dawies and Kara Leitner, World Trade Law: Text, Materials and Commentary Markus Krajewski Rüdiger Wolfrum, Peter-Tobias Stoll and Clemens Feinäugle, WTO: Trade in Services, Max Planck Commentaries on World Trade Law, Vol. 6 Christoph Ohler Part V: Materials Opinion of Advocate General Kokott Delivered on 26 March 2009 Juliane Kokott
Includes bibliographic references
Electronic reproduction
Keywords: Commercial law; Commercial law -- Europe; International law; International economic relations; International finance -- Law and legislation